Evaluating Dihydroazulene/Vinylheptafulvene Photoswitches for Solar Energy Storage Applications. Issue 15 (19th July 2017) - Wang, Zhihang; Udmark, Jonas; Börjesson, Karl; Rodrigues, Rita; Roffey, Anna; Abrahamsson, Maria; Nielsen, Mogens Brøndsted; Moth‐Poulsen, Kasper
Abstract: Efficient solar energy storage is a key challenge in striving toward a sustainable future. For this reason, molecules capable of solar energy storage and release through valence isomerization, for so‐called molecular solar thermal energy storage (MOST), have been investigated. Energy storage by photoconversion of the dihydroazulene/vinylheptafulvene (DHA/VHF) photothermal couple has been evaluated. The robust nature of this system is determined through multiple energy storage and release cycles at elevated temperatures in three different solvents. In a nonpolar solvent such as toluene, the DHA/VHF system can be cycled more than 70 times with less than 0.01 % degradation per cycle. Moreover, the [Cu(CH3 CN)4 ]PF6 ‐catalyzed conversion of VHF into DHA was demonstrated in a flow reactor. The performance of the DHA/VHF couple was also evaluated in prototype photoconversion devices, both in the laboratory by using a flow chip under simulated sunlight and under outdoor conditions by using a parabolic mirror. Device experiments demonstrated a solar energy storage efficiency of up to 0.13 % in the chip device and up to 0.02 % in the parabolic collector. Avenues for future improvements and optimization of the system are also discussed. Abstract : MOST excellent ! Photoconversion of the dihydroazulene/vinylheptafulvene (DHA/VHF) photothermal couple through multiple energy storage and release cycles enables its usage as a molecular solar thermal energy storage (MOST) system. In toluene, the DHA/VHF system can be cycled more than 70 times with less than 0.01 % degradation per cycle. The performance of this couple is also evaluated in prototype photoconversion devices.